Guava seedlings with rootstocks or interstocks and their reaction to salinity - Souza, Alexandre Gomes de; Marinho, Claudia Sales; Soares da Silva, Mirian Peixoto; Gomes Carvalho, Waleska Soares [UNESP]; Campos, Graziella Siqueira; Pestana, Bruno Abreu (Inst Agronomico, 2020)
The introduction of rootstocks for the guava has become necessary due to the advance of guava decline. Among them, Psidium spp. or their hybrids have been evaluated. In addition to disease resistance, tolerance to salinity must be evaluated in the new rootstocks. The aim of this study was to verify the effect of rootstocks and intergrafts on the mineral composition of Psidium spp. submitted to salt stress. The experiment was setup in a randomized block design, with the following treatments (scion/rootstock): P. guineense/P. cattleianum; P. guajava/P. guineense/P. cattleianum; P. guajava 'Paluma'/P. guajava; P. guajava 'Paluma'/P. guineense; P. guajava 'Cortibel 1'/P. guajava; P. guajava 'Cortibel 1'/P. guineense; P. cattleianum (purple) and P. cattleianum (yellow), with three replications and three plants per plot. The plants underwent irrigation with saline solution, and the levels of macronutrients, micronutrients and sodium in the scion leaves were evaluated. As rootstock, P. cattleianum results in greater Na uptake, with higher levels in the leaves of the scions, leading to less tolerance to salt stress.
Keywords: accumulation of sodium in leaves; mineral nutrient contents in Psidium spp.; interstocked seedlings